Integrated clinical treatment of external cervical resorption: Case report (Research, Society and Development, 2021)
External cervical resorption (ECR) has an inflammatory nature and the proximity to the gingival sulcus favors contamination and progression of the lesion. Change in crown color, inflammation of the marginal gingiva or even the presence of secretion in the gingival sulcus are the main clinical signs. Being an asymptomatic lesion, it can be neglected and its progression can jeopardize the tooth involved. This report describes the treatment of a patient who presented two teeth with ECR. On clinical examination, the crown of tooth 17 showed a pinkish translucency on the occlusal surface. On tooth 12, this spot was dark and located in the cervical third of the labial surface of the crown. Both the teeth were asymptomatic, and the radiographic examination showed an image comparable with root resorption in the cervical third of the crown.  On tooth 17, the middle and cervical third of the crown was compromised and the pulp vitality test was negative. The treatment for the case was extraction. A tomographic examination of tooth 12 demonstrated pulpal involvement and biologic width violation. The vitality test was positive. After endodontic treatment, the tooth was extruded by 4 mm, the resorbed area was exposed and restored with composite resin. A 39-month clinical and radiographic control showed integrity of the root surface and the periodontium. It was found that early diagnosis influences the prognosis of treatment considering the speed of progression of resorption. It emphasizes the importance of clinical and radiographic control of the clinical conditions that predispose to ECR.